Estrategias metodológicas y el desarrollo de la destreza lectora, en los estudiantes de tercer grado de la escuela de EGB. José Ingenieros, del cantón Loja, periodo 2018- 2019. Lineamientos Alternativos - Lopez Patiño, Blanca Juleysi (2019)
The present research work called Methodological Strategies and the development of reading skills, in the third grade students of the EGB School. José Ingenieros, from the Loja canton, period 2018-2019. Alternative Guidelines have as a general objective: Analyze the methodological strategies for the development of reading skills in the third grade students of the EGB School. José Ingenieros, from the Loja canton, 2018-2019 period. The type of study is descriptive, non-experimental design, observational, descriptive, inductive, deductive, hermeneutic, analytical, synthetic, statistical and theoretical methods applied; the techniques: survey; questionnaire instrument; diagnostic procedures, theoretical foundation, alternative guidelines; as a result it was evident that the teacher does not use methodological strategies in teaching for the development of reading skills, which has generated students' disinterest in their learning. In the research work, 28 third grade students and one teacher participated. As a conclusion, the methodological strategies allow the development of reading skills in students, for this reason it is important to apply them during the learning process.